PEMBELAJARAN IPA DENGAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN PROSES SAINS SISWA SD TAHUN 2026 - Munir Latukau (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
This study aims to examine the effect of using a guided inquiry learning model on improving elementary school students' conceptual understanding and science process skills in the topic of simple machines. The study used an experimental method involving two fifth-grade classes at a public elementary school in Ternate City, North Maluku. The experimental class, consisting of 40 students, received instruction using the guided inquiry model, while the control class, consisting of 40 students, received instruction using the conventional model. Data were collected using conceptual understanding tests, science process skills tests, student response questionnaires, and teacher interviews. The tests were objective-based to measure students' conceptual understanding and science process skills. The data were analyzed using standard statistical analysis techniques to determine differences in learning outcomes between the two groups. The results showed that the application of the guided inquiry learning model significantly improved students' conceptual understanding and science process skills compared to the conventional learning model. Students learning through the guided inquiry model demonstrated better abilities in understanding science concepts and developing science process skills. Furthermore, the results of the questionnaire and interviews indicated that teachers and the majority of students responded positively to the use of this learning model. They felt more motivated, active, and engaged in the learning process. The guided inquiry model was also deemed to facilitate conceptual understanding and the development of science process skills more effectively. Therefore, this model is recommended for application to other science subjects in elementary schools.